Evaluation of choroidal thickness measurements in pediatric obstructive sleep apnea syndrome patients - Bayraktar, Cem; Şimşek, Ali (The Turkish Journal of Pediatrics, 2017)
Choroidal vascular impairment and obstructive sleep apnea syndrome (OSAS) related disorders have been shown in adults, but there have been no investigations with regard to the choroidal thickness measurements in children with OSAS. Our aim was to investigate this relationship in the early childhood period, which correlates with OSAS peak incidence due to adenotonsillar enlargement. One-hundred and nine pediatric OSAS patients and 42 age-sex matched controls were enrolled in this study. Nocturnal pulse oximetry was used to define the OSAS patients. Demographic data like age, sex and body-mass index were recorded. All of the subjects underwent complete otolaryngologic and ophthalmologic examination including visual acuity, intraocular pressure, central corneal thickness, axial length and choroidal thickness measurements. Overall, the 1,000 μm and 1,500 μm nasal choroid measurements were found to be significantly lower in the patient group (p < 0.05). However, only a poor inverse correlation emerged between the body-mass index (BMI) and the foveal center measurements in the patients. Observed alterations in the choroid may signify the initial impairment of known OSAS-related eye disorders, like glaucoma, floppy eyelid syndrome, and non-arteritic ischemic optic neuropathy. Ophthalmologists, otolaryngologists and pediatricians working together as a team may be able to prevent future eye diseases.
Keywords: adenotonsillar hypertrophy; choroid; nocturnal pulse oximetry; sleep apnea